Saccos’ Financial Services and Growth of Members’ Enterprises in Luweero District in Uganda - Mpubani, David Dickens; Kintu, Ismail; Turyakira, Peter (International Journal of Business Marketing and Management (IJBMM), 2020)
The purpose of the study was to establish the relationship between SACCOs’ financial services (savings and credit facility) and growth of members’ enterprises (sales). The survey method was employed in Luweero District using a structured questionnaire. The sample size comprised 200 SACCO members who operate Small Scale Enterprises and obtained credit from the SACCOs. Data were analysed by descriptive statistics, Pearson’s correlation method and multi test regression technique. The regression results indicate a significant positive relationship between savings and growth of SACCO members’ enterprises while the relationship between credit services and growth of SACCO members’ enterprises was positive but insignificant. Based on the results, SACCOs may improve interest rates on savings as a way of motivating members to work hard for more savings. By equipping credit management skills to SACCO managers, SACCOs can ensure members’ satisfaction whenever they obtain credit from the SACCOs.
Keywords: SACCOs; Savings; Credit; SACCO members’ enterprises and growth